Perioperative antibiotic prophylaxis in radical prostatectomy: “single-shot” versus multiday regimen - Hartung, Friedrich; Herrmann, Jonas; Kowalewski, Karl-Friedrich; Neuberger, Manuel; Weiß, Christel; Kriegmair, Maximilian; Michel, Maurice Stephan; Ritter, Manuel; Rassweiler-Seyfried, Marie-Claire (Urologia internationalis, 2023)
Introduction: Perioperative antibiotic prophylaxis (AP) is common in radical prostatectomy (RP). Yet there is no standard recommendation in international guidelines due to poor evidence. It is of great importance that these perioperative AP are sufficiently checked and systemically validated. The objective of this study was to determine whether a “single-shot” (single-use) perioperative AP yields equivalent results compared to a multiday prophylaxis in RP regarding postoperative wound infections and urinary tract infections. Methods: 376 patients treated by RP at the University Medical Centre Mannheim, from 2014 to 2016, were included in this retrospective study. RP was performed either in a robotic-assisted or open manner. One group received an intravenous dose of perioperative AP with either ciprofloxacin or levofloxacin, continued by an oral dose of AP with ciprofloxacin or levofloxacin until catheter removal, while the other group received a single-shot intravenous perioperative AP with either ciprofloxacin or cefuroxime. Results: There was no significant difference regarding the occurrence of postoperative infections between both AP regimes (p = 0.5). Age, body mass index, and ASA classification did not differ significantly between both groups (p > 0.25). Except for surgery time (p < 0.05), perioperative parameters, such as the preoperative presence of germ-free urine culture, length of hospital stay, catheter time, drain lay time, Gleason score, and TNM stadium, did not differ significantly. Conclusion: The present study shows that perioperative single-shot AP does not entail any disadvantage compared to the multiday AP in terms of postoperative infections after RP.
Im Titel ist "single-shot" in Anführungszeichen geschrieben
Online veröffentlicht: 14. Dezember 2022
Gesehen am 25.06.2024